Nitrogen Removal from Wastewater by an Aerated Subsurface‐Flow Constructed Wetland in Cold Climates. (1st April 2014) - Redmond, Eric D.; Just, Craig L.; Parkin, Gene F.
ABSTRACT: The objective of this study was to assess the role of cyclic aeration, vegetation, and temperature on nitrogen removal by subsurface‐flow engineered wetlands. Aeration was shown to enhance total nitrogen and ammonia removal and to enhance removal of carbonaceous biochemical oxygen demand, chemical oxygen demand, and phosphorus. Effluent ammonia and total nitrogen concentrations were significantly lower in aerated wetland cells when compared with unaerated cells. There was no significant difference in nitrogen removal between planted and unplanted cells. Effluent total nitrogen concentrations ranged from 9 to 12 mg N/L in the aerated cells and from 23 to 24 mg N/L in unaerated cells. Effluent ammonia concentrations ranged from 3 to 7 mg N/L in aerated wetland cells and from 22 to 23 mg N/L in unaerated cells. For the conditions tested, temperature had only a minimal effect on effluent ammonia or total nitrogen concentrations. The tanks‐in‐series and the PkC * models predicted the general trends in effluent ammonia and total nitrogen concentrations, but did not do well predicting short‐term variability. Rate coefficients for aerated systems were 2 to 10 times greater than those for unaerated systems.